The effect of Foliar Application of Boron and Zinc on physical and chemical characterizations of fruit the Orange tree (Valencia variety) (Latakia University Journal -Biological Sciences Series, 2019)
The experiment was conducted in Zarkat village of Tartous governorate during the two seasons (2017 , 2018 ) on orange cv (Valencia) to study the effect of the foliar spraying with the nutrients (boron and zinc) on physical and chemical properties of orange cv (Valencia). These nutrients were sprayed separately or as a mixture using different concentrations. The average of each physical property (width, volume and weight of the fruit ), as well as rind thickness and fruit juice amount was calculated. The chemical properties of fruit juice (total soluble solids, total acidity, vitamin C) were also studied. The results of the statistical analysis showed that the foliar spraying with boron and zinc on orange cv (Valencia) improved the quality of fruits in terms of physical traits The treatment of boron and zinc spraying at high concentration (200 ppm B, 300 ppm Zn) gave the highest average weight of the fruit during the first and second seasons, i.e. (194.48 g), while it didn't exceed 176.36 g for the control. Boron and zinc treatment significantly outperformed nutrition treatments separately. It also improved the chemical properties of the fruits in terms total soluble solids (11.25%), total acidity (2.43 mg%) and vitamin C (49.21 mg%). The treatment of foliar spraying with boron and zinc at concentration (200ppm B, 300ppm Zn) predominated other treatments including the control. نفذت التجربة في قرية الزرقات التابعة لمحافظة طرطوس خلال موسمين زراعيين (2017 و 2018) بهدف دراسة تأثير التغذية الورقية بعنصري (البورون و الزنك) في الصفات الفيزيائية والكيميائية لثمار أشجار البرتقال صنف "فالنسيا"، ورشت هذه العناصر بشكل منفرد أو على شكل خليط وبتراكيز مختلفة. تم حساب متوسط كلاً من ( قطر الثمرة ووزنها وحجمها)، علاوة على ذلك حجم العصير وسماكة قشرة الثمرة، كما درست الصفات الكيميائية لعصير الثمار (المواد الصلبة الذائبة الكلية، الحموضة الكلية، فيتامين(C . بينت نتائج التحليل الإحصائي أن التغذية الورقية بالبورون والزنك لأشجار صنف البرتقال "فالنسيا" حسن من نوعية الثمار من حيث صفاتها الفيزيائية؛ إذْ حققت معاملة الرش بالبورون والزنك معا بتركيز (200جزء بالمليون B، 300 جزء بالمليون Zn) أعلى متوسط لوزن الثمرة خلال الموسمين الأول والثاني؛ إذْ بلغ متوسط اوزن الثمرة لعامين (194.48 غ)، بينما لم يتجاوز 176.36غ في الشاهد. وقد تفوقت معاملات التغذية بالبورون والزنك معاً معنوياً على معاملات التغذية بهما بشكل منفرد. وحسنت أيضاً الصفات الكيميائية للثمار من حيث نسبة المواد الصلبة الذائبة الكلية (11.25%)، ونسبة الحموضة (2.43 ملغ%)، ونسبة فيتامين C (49.21 ملغ%)، وقد تفوقت معاملة التغذية الورقية بالبورون والزنك معاً بتركيز (200جزء بالمليون B ، 300 جزء بالمليون Zn) على بقية المعاملات بما فيها الشاهد.